2022
DOI: 10.1093/cid/ciac246
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Reinfection Following Direct-Acting Antiviral Treatment in the Prison Setting: The SToP-C Study

Abstract: Background Injection drug use (IDU) following treatment for hepatitis C virus (HCV) may lead to reinfection, particularly if access to harm reduction services is suboptimal. This study assessed HCV reinfection risk following direct-acting antiviral therapy within Australian prisons that had opioid agonist therapy (OAT) programs but did not have needle and syringe programs (NSP). Methods The Surveillance and Treatment of Priso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…/100 PY). 14,17,19 We observed similar findings in the current study, with 15% of individuals treated in our 3 prisons having reinfection aftertreatmentandtheincidenceratewas14.5/100PY.Inaddition, 50% of the patients identified with reinfection had blood testing in the prison setting. This high proportion is probably due to the more comprehensive testing programme that occurs in prisons as blood borne virus testing is offered to all individuals entering the prisons in our region.…”
Section: Wealsofoundthatindividualswithprimarygenotype3weremoresupporting
confidence: 87%
See 2 more Smart Citations
“…/100 PY). 14,17,19 We observed similar findings in the current study, with 15% of individuals treated in our 3 prisons having reinfection aftertreatmentandtheincidenceratewas14.5/100PY.Inaddition, 50% of the patients identified with reinfection had blood testing in the prison setting. This high proportion is probably due to the more comprehensive testing programme that occurs in prisons as blood borne virus testing is offered to all individuals entering the prisons in our region.…”
Section: Wealsofoundthatindividualswithprimarygenotype3weremoresupporting
confidence: 87%
“…Previous studies have shown that HCV reinfection frequently occurs among individuals treated in the prison setting 14,17,19 . Rates of HCV reinfection after antiviral treatment range from 8.14 to 14.3 /100 PY in Scotish prisons and were 12.5 /100 PY in a study from 4 Australian prisons, but rates were markedly higher in individuals who reported recent injecting drug use and needle/syringe sharing (28.7 /100 PY) 14,17,19 .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, there was still a high rate of HCV‐RNA positivity (6%) at reception and a significant incidence of new HCV infection (5.1 and 3.3 per 100 person‐years for HCV‐Ab and HCV‐RNA positivity, respectively) and reinfection (10.2 per 100 person‐years) indicating a large burden of untreated HCV in the community. These findings are in keeping with previous work showing, a high frequency of reinfection following antiviral treatment in people treated in the prison setting 13,19–21 . This underscores the need for all prisons to provide good harm minimisation education to all people who inject drugs that is reinforced at the time of release.…”
Section: Discussionsupporting
confidence: 89%
“…Secondly, this study used HCV antibody results and incidence rates did not include re-infection. This may have resulted in an underestimation of the incidence of all new HCV infections, particularly in the post-DAA time-period, where re-infection has been demonstrated in Australia [27,28]. Similarly, incidence of primary HCV infection may have been be underestimated in the pre-DAA time-period, where receptive sharing of syringes, a significant risk factor for HCV transmission [16], was higher among respondents with a single survey record than those retained in our data set.…”
Section: Discussionmentioning
confidence: 99%